Populism, Artificial Intelligence and Law: A New Understanding of the Dynamics of the Present - Grant, David (Routledge, 2025)
Political systems across much of the West are now subject to populist disruption, which often takes an anti-Constitutional form. This interdisciplinary book argues that the current analysis of anti-Constitutional populism, while often astute, is focused far too narrowly. It is held here that due to an obscured complex of dynamics that has shaped the history of the West since its inception and which remains active today, we do not understand the present. This complex not only explains the current disruptions across the fields of contemporary religion, politics, economics and emerging artificial intelligence but also how these disruptions derive each from originary sources. This work thereby explains not only the manner in which this complex has functioned across historical time but also why it is that its inherent, unresolvable flaws have triggered the shifts between these key fields as well as the intractability of these present disruptions. It is this flawed complex of factors that has led to current conflicts about abortion reform, political populism, the failure of neoliberalism and the imminent quantum shift in generative artificial intelligence. It is argued that in this, law is heavily implicated, especially at the constitutional level. Presenting a forensic examination of the root causes of all these disruptions, the study provides a toolbox of ideas with which to confront these challenges. This is a book of originality and significance, which will make fascinating reading for academics and researchers working in the areas of Socio-legal Studies, Legal Philosophy, Political Science, Theology, AI and Neuroscience. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.